2013
DOI: 10.1001/dmp.2011.36
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among Nurses Caring for Victims of War in Sri Lanka

Abstract: AbstractObjectiveTo determine prevalence and factors associated with psychological distress among nurses caring for war victims in Sri Lanka.MethodsDescriptive, cross-sectional study design was used to collect data from 241 nurses from 2 hospitals with stratified random sampling according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
12
3
Order By: Relevance
“…In contrast to the other study, this study was found to be higher compared with the studies conducted in different areas, wherein Norwegian 13% [40], in Sri Lanka 21% [41], in Addis Ababa, Ethiopia 11.7% [42], and in another study conducted in Addis Ababa, Ethiopia 17.7% [43].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the other study, this study was found to be higher compared with the studies conducted in different areas, wherein Norwegian 13% [40], in Sri Lanka 21% [41], in Addis Ababa, Ethiopia 11.7% [42], and in another study conducted in Addis Ababa, Ethiopia 17.7% [43].…”
Section: Discussioncontrasting
confidence: 99%
“…Most of the reviewed studies into the challenges affecting oncology nurses were conducted in developed countries . However, a few studies were conducted in developing countries . No studies were conducted in Middle Eastern countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the rapidly ageing population, a shift in disease burden towards non‐communicable diseases, and Sri Lanka's need for disaster management preparedness for environmental disasters such as landslides, floods, and tsunamis, limited opportunities exist for relevant field programmes for nurses (Jayawardene et al. ). Nursing education (diploma level) for nurses in the public sector is free, and students receive a stipend.…”
Section: Nursing Educationmentioning
confidence: 99%
“…Limited post-registration specialized diplomas in management, teaching and supervision, nursing education, and public health, as well as courses in midwifery and clinical specialties such as psychiatric nursing, are offered by the MOH. Despite the rapidly ageing population, a shift in disease burden towards non-communicable diseases, and Sri Lanka's need for disaster management preparedness for environmental disasters such as landslides, floods, and tsunamis, limited opportunities exist for relevant field programmes for nurses (Jayawardene et al 2013). Nursing education (diploma level) for nurses in the public sector is free, and students receive a stipend.…”
Section: Nursing Educationmentioning
confidence: 99%